BEBERAPA FAKTOR YANG MEMPENGARUHI PERINGKAT OBLIGASI PERUSAHAAN NON-KEUANGAN DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Situmorang, Paulina Octavia; Silalahi, Donalson (UNIKA Santo Thomas, 2022)
This study was conducted to determine the effect of several factors that affect the ratings of non-financial company bonds that have gone public on the Indonesian stock exchange. To achieve this purpose, a study was conducted with a research period of 2017 – 2020 and used purposive sampling as a sampling method and the data were analyzed using multiple regression analysis. The results showed that partially the current ratio had no significant effect on bond ratings, the ratio of debt to equity had a negative and significant effect on bond ratings, and the ratio of net income to total assets had a positive and significant effect on bond ratings. The ability of the three ratios in explaining bond ratings is 51.3 percent.